Experimental analysis of energy consumption of building roof energy-saving technologies based on time difference comparison test - Zhao, Shanguo; Hai, Guangmei; Ma, Hongtao; Zhang, Xiaosong (Frontiers in Energy Research, 2023)
The roof plays a pivotal role as it directly engages with solar radiation absorption and external heat exchange, significantly influencing the building’s overall energy dynamics. To assess the performance of green roofs and cool roofs, a roof performance test facility was established in Nanjing. Time-difference comparison experiments were conducted to measure and analyze the energy-saving effects of cool roofs, green roofs, and conventional roofs during both summer and winter conditions. The study aimed to investigate how their thermal performance impacts building energy consumption. The study’s findings reveal that under summer conditions, the incorporation of a cool roof system leads to a substantial enhancement in energy efficiency, achieving an impressive 13.2% energy savings compared to conventional roofing solutions. In contrast, the implementation of a green roof system results in a more modest energy-saving rate of 4.1%. Transitioning to winter conditions, the adoption of a cool roof system shows a marginal increase of 2.8% in energy consumption compared to conventional roofs. Interestingly, the green roof system stands out as an energy-efficient option during winter, demonstrating a significant 4.9% reduction in energy consumption. This approach ensured reliable and valid results to provide a comprehensive view of how different roof types respond to varying climatic conditions.